Aku Tidak Peduli, Walaupun Aku Harus Mati untuk Mengejar Impianku : (Study Fenomenologis Fanatisme Otaku) - Juwita Putri Andini; Dela Oktari (Institut Nalanda, 2025)
Anime is currently becoming popular among people in various parts of the world including Indonesia, many people like anime and some are even fanatical about anime. Based on this, the researcher conducted a study that aimed to find out how fanatical the three participants were towards anime. .The sample in this study was 3 people using a purposive sampling technique. The data collection method was through semi-structured interviews and then interview transcripts were analyzed using Interpretative Phenomenological Analysis (IPA). There are two superordinate themes found, namely: self-change and the search for identity. The implication of this research is to find out how anime fanatics or also known as otaku affect the personal identity of the participants, to find out how the participants face challenges in finding their identity amidst social pressures and excessive expectations from the surrounding environme without ignoring the participants’ interest and interest in otaku culture.